Amorphous polyester composition and method of preparation
Patent Information
- Application Number
- JP2021557630
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-27
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2040-03-27
Smart Images

Figure 0007651468000001 
Figure 0007651468000002 
Figure 0007651468000003
Abstract
Description
[Technical field]
[0001] Described herein are compositions and methods for making amorphous polyester compositions that can be converted into low density foams suitable for use as insulation materials in building and other industrial applications. Summary of the Invention [Problem to be solved by the invention]
[0002] Crystalline and semi-crystalline polyester polymers cannot be easily foamed to produce low density foams because their crystalline or semi-crystalline nature means that high temperatures are required to keep the material from recrystallizing while the trapped gas expands to produce the foam. In the molten state, above its recrystallization temperature, the viscosity and melt strength of semi-crystalline polyesters such as PET are too low to allow the bubbles to expand significantly before curing. This limits the foam density that can be achieved (e.g., 96 kg / m 3 (The current invention is limited to higher density foams, characterized by densities above 6 pcf.) The present invention solves the problem of foaming crystalline or semi-crystalline polyesters to produce low density foams, such as polyethylene terephthalate (PET), by converting the polyester into an amorphous copolyester polymer material that can produce low density foams from the polymer melt or from extruded expandable beads containing a suitable blowing agent.
[0003] In the manufacture of expandable polyesters or copolyesters derived from semicrystalline PET, the starting materials can be sourced as virgin materials or from "recycled" waste streams such as PET bottles and other post-consumer PET sources. For purposes of this invention, "recycled" refers to both post-consumer and post-industrial waste materials. Thus, one particularly desirable objective is to utilize recycled semicrystalline PET and convert it into an amorphous, non-easily crystallizable polymer that can be expanded to produce low density foams. Thus, there is a need for expandable compositions comprising amorphous polymers derived from virgin or recycled crystalline or semicrystalline polyesters, methods of preparing the amorphous polymers and expandable compositions, and methods of using them. The present invention is directed to these and other important objectives. [Means for solving the problem]
[0004] Optionally, the amorphous polyester or copolyester composition comprises the reaction product of a crystalline or semi-crystalline polyester or copolyester obtained from a recycled waste stream, at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride, and a catalyst, wherein the amorphous composition has a weight average molecular weight of at least 10,000 g / mole (polystyrene equivalent molecular weight) as measured by gel permeation chromatography.
[0005] The method of making the amorphous polyester resin described herein comprises the following steps: combining crystalline or semi-crystalline polyester, optionally obtained from recycled waste streams, with at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride in a reactor at room temperature in the presence of a catalyst; sealing and purging the reactor with an inert gas; mixing the contents; venting volatile components from the reactor; flushing the reactor with an inert gas at least once; increasing the temperature of the reactor to 250-350° C. for a period of 30-90 minutes; mixing a combination of molten materials; maintaining a temperature of 250-350°C; evacuating the reactor to below minus 25 inches of mercury; continuing the reaction at a temperature of 250-350° C. for 100-300 minutes, optionally removing volatile species via a distillation column; and quenching the reaction by stopping mixing, purging the reactor with an inert gas, returning the reactor to atmospheric pressure, and reducing the temperature to 100° C. or less, wherein the resulting composition has a weight average molecular weight of at least 10,000 g / mole (polystyrene equivalent molecular weight) as measured by gel permeation chromatography, and a crystallinity of 5% or less as determined by differential scanning calorimetry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] In the case of semi-crystalline PET, where the polymer consists essentially of ethylene terephthalate repeat units, foaming must be performed above the crystallization temperature. For PET, this temperature is typically between the normal melting point (about 250°C) and the onset temperature of crystallization of PET when cooled from the molten state (about 150°C), both temperatures determined by differential scanning calorimetry (DSC) at heating and cooling rates of 10°C / min. At such high temperatures, molten PET has very low melt strength and can only expand minimally before the onset of vitrification caused by crystallization. As disclosed herein, PET (virgin or recycled) is in an amorphous, not easily crystallizable form. The exclusion of crystallization allows melt processing of the polymer below 150°C, where both melt strength and viscosity are higher. This promotes bubble expansion and limits bubble coalescence, allowing the preparation of low density foamed products. However, the exclusion of crystallinity in the neat form of the polymer is necessary, but not sufficient for foamability. The addition of one or more soluble blowing agents enhances the crystallization rate. Specifically, the type of polymer chain structure required to sufficiently slow down the crystallization rate in the presence of such blowing agents (e.g., carbon dioxide, etc.) to promote foaming is further disclosed herein. This is the case for polymers having a crystallization rate of 96 kg / m 3 (6pcf), more preferably less than 80kg / m 3 and even more preferably a density of less than 40 kg / m 3 This is a necessary attribute for the polymer to be adequately foamable at temperatures below 150° C. to achieve densities below (2.5 pcf).
[0007] Unlike semi-crystalline PET, which is known to have low solubility in typical blowing agents, the process of the present invention modifies PET to produce an amorphous polymer that has higher solubility in typical blowing agents, allowing for the preparation of low density foamed articles. Preventing the formation of crystalline structures also increases gas permeability, which is also favorable for bubble growth during the foaming process.
[0008] Both virgin and recycled PET can be made conducive to foaming by reducing or eliminating their ability to crystallize in the presence of heat and / or dissolved gases. This is achieved by direct transesterification of molten PET with one or more monomers in the presence of a catalyst, promoting rearrangement and ordering of the types of repeat units contained within the polymer to form new random copolyesters. The new monomer components may include organic esters, diols, diacids, dianhydrides, hydroxycarboxylic acids, or lactones. The compositions may include polyols, polyacids, or polyanhydrides, or other multifunctional species aimed at introducing long chain branching. Since esterification is an equilibrium reaction, it may be necessary to continuously remove water or alcohol or ethylene glycol to drive the transesterification reaction to high conversions. By appropriate selection of reaction conditions such as catalyst, temperature, reaction time, and application of vacuum, the crystallization rate of the resulting polymer is sufficiently slow. This reduction or elimination of crystallization allows processing at temperatures below 150°C (the typical crystallization onset temperature of the starting PET material). The final copolyester can be melt blended with a physical blowing agent and expanded by extrusion foaming or rapidly cooled and pelletized to form beads for subsequent expansion.
[0009] The term "polyester" in this specification refers to a polymer whose repeating units are characterized by an ester group in the backbone of the polymer. Thus, the term includes not only typical polyesters prepared from one diacid component and one dihydroxy component, but also esters of diacids, or hydroxycarboxylic acids, lactone-based polyesters, or dianhydrides, and copolymers, i.e., polyesters composed of at least two acid components and / or alcohol components, and / or hydroxycarboxylic acid components and / or lactone components ("copolyesters"). The term "copolyester" is a subset of polyester.
[0010] As used herein, the term "foam" refers to a low-density matrix of a fluid or solid that contains a plurality of finely divided pores or bubbles. Foams can be closed-cell or open-cell, terms well known in the art. Depending on the context, the term herein can refer to an initial foam formed from a molten polymer, or can be used to describe a final solidified foam. With regard to determining whether a sample can be successfully foamed ("foamable resin" or "foamable composition"), the initial or molten sample can be foamed (by a specific method and / or under specific conditions) to form a stable foam. The foamed article can further include one or more additives in any combination. Exemplary additives include infrared attenuators (e.g., carbon black, graphite, metal flakes, titanium dioxide), clays such as natural absorbent clays (e.g., kaolinite and montmorillonite) and synthetic clays, nucleating agents (e.g., talc and magnesium silicate), flame retardants (e.g., flame retardant packages that may include brominated flame retardants such as hexabromocyclododecane and brominated polymers and copolymers, phosphorus flame retardants such as triphenyl phosphate, and synergists such as dicumyl and polycumyl), lubricants (e.g., calcium stearate and barium stearate), and acid scavengers (e.g., magnesium oxide and tetrasodium pyrophosphate). Preferably, the thermoplastic polymer foam article includes an infrared attenuator to minimize thermal conductivity through the article. The additives are typically dispersed within the polymer matrix, generally within the continuous thermoplastic polymer phase, and are present at a concentration of up to 15% by weight based on the total polymer weight in the polymer foam article.
[0011] As used herein, "stable foam" refers to a foam that is stable with respect to observable shrinkage or collapse during and thereafter the solidification process in the absence of external forces other than the surrounding atmosphere.
[0012] As used herein, the term "rigid foam" refers to a solidified foam having a cellular structure with a compressive strength greater than 5 psi.
[0013] All molecular weights and other values related to molecular weight (such as polydispersity index) disclosed herein are determined by GPC.
[0014] As used herein, "number average molecular weight" (M n or
number
number
[0015] As used herein, "weight average molecular weight" (Mw, or
number
number
[0016] Amorphous polyester or copolyester resin The amorphous polyester or copolyester composition comprises a crystalline or semi-crystalline polyester or copolyester, optionally obtained from recycled waste streams; at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride; Catalyst and comprising the reaction product of The amorphous polymeric reaction product herein has a weight average molecular weight of at least 10,000 g / mole (polystyrene equivalent molecular weight) as measured by gel permeation chromatography.
[0017] In some embodiments, the polyester is polyethylene terephthalate, polyethylene terephthalate glycol, or a polyester whose major diol component is ethylene glycol, propylene glycol, 1,4-butanediol, spiro glycol, or blends thereof.
[0018] In some embodiments, the at least one aromatic diacid monomer is phthalic acid, terephthalic acid, isophthalic acid, or 2,5-furandicarboxylic acid, or a combination thereof.
[0019] In some embodiments, the at least one diol is isosorbide, cyclohexane, dimethanol, or cyclobutanediol. In some such embodiments, the cyclohexanedimethanol is 1,4-cyclohexanedimethanol present in an amount of 20-40 mol % of the total diol content, the isosorbide is present in an amount of 15-100 mol % of the total diol content, and the cyclobutanediol is 2-2-4-4-tetramethyl-1-3-cyclobutanediol present in an amount of 45-55 mol % of the total diol content.
[0020] In one embodiment, the cyclohexanedimethanol is 1,3 cyclohexanedimethanol, 1,4 cyclohexanedimethanol, or blends thereof, present in an amount of 20-30 mole percent in combination with isophthalic acid, present in an amount of 20-30 mole percent.
[0021] Suitable catalysts for the transesterification reaction include those known in the art, in particular organometallic complexes such as, for example, titanium tetrabutoxide, Ti(OBu)4, cerium(III) acetate, Ce(OAc)3, tetraisopropyl titanate, and tin-based organometallic complexes commercially available under the trade name FASCAT® catalyst (PMC Organometallics, Mount Laurel, NJ, USA). A preferred catalyst is antimony trioxide. Suitable use concentrations may vary from catalyst to catalyst, and generally range from 50 ppm to 10,000 ppm, or from 1,000 ppm to 5,000 ppm, or from 1,500 ppm to 3,000 ppm (parts by weight of catalyst per million parts of total polymer present in the reaction).
[0022] Preferably, the amorphous resin has a crystallinity of 5% or less, or even 1% or less, a maximum heat of fusion of less than 7 J / g, or even less than 1 J / g, and a glass transition temperature (Tg) of at least 75°C, or at least 85°C, or at least 90°C, or at least 100°C, or at least 110°C.
[0023] Method for preparing amorphous polyester or copolyester resin The method of making the amorphous polyester resins described herein comprises the steps of: combining crystalline or semi-crystalline polyester, optionally obtained from recycled waste streams, with at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride in a reactor at room temperature in the presence of a catalyst; sealing and purging the reactor with an inert gas; mixing the contents; venting volatile components from the reactor; flushing the reactor with an inert gas at least once; increasing the temperature of the reactor to 250-350°C, such as 280-290 or 283-287°C, over a period of 30-90 minutes, such as 50-70 minutes, or 55-65 minutes, or even 58-63 minutes; mixing the combination of molten materials at a speed of, for example, 100 to 200 rpm; maintaining a temperature of 250 to 350°C, such as 280 to 290°C or 283 to 287°C, for a holding time of 20 to 200 minutes, 20 to 150 minutes, or 40 to 100 minutes; evacuating the reactor to below minus 25 inches of mercury; continuing the reaction at a temperature of 250-350° C., 280-290° C., or 283-287° C. for 100-300 minutes, 200-220 minutes, or 208-212 minutes, optionally removing volatile species via, for example, a distillation column; and stopping the reaction by stopping mixing, purging the reactor with an inert gas, returning the reactor to atmospheric pressure, and reducing the temperature to below 100° C.; The resulting composition has a weight average molecular weight (as measured by gel permeation chromatography, in terms of polystyrene) of at least 10,000 g / mole, and a crystallinity of 5% or less, or 1% or less, as determined by differential scanning calorimetry.
[0024] In some embodiments, the retention time is 40 to 50 minutes, or even 43 to 47 minutes, in other embodiments, the retention time is 80 to 100 minutes, more preferably 85 to 95 minutes, or most preferably 87 to 93 minutes.
[0025] Another method for making an amorphous polyester resin is to Incorporating a crystalline or semi-crystalline polyester, optionally obtained from a recycled waste stream, with at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride in a reactor at room temperature in the presence of a catalyst; sealing and purging the reactor with an inert gas; mixing the contents; venting volatile components from the reactor; flushing the reactor with an inert gas at least once; increasing the temperature of the reactor to 250-350°C or 280-290°C or 283-287°C over a period of 30-90 minutes or 50-70 minutes, preferably 55-65 minutes or even 58-63 minutes; mixing the combination of molten materials at a speed of, for example, 100 to 200 rpm; maintaining a temperature of 250 to 350° C. or 280 to 290° C., preferably 283 to 287° C., for a holding time of 20 to 150 minutes or 40 to 100 minutes; evacuating the reactor to below minus 25 inches of mercury; continuing the reaction at a temperature of 250-350° C. or 280-290° C., preferably 283-287° C., for 100-300 minutes, or 200-220 minutes, preferably 208-212 minutes, optionally removing volatile species, for example via a distillation column; quenching the reaction by ceasing mixing, purging the reactor with an inert gas, and returning the reactor to atmospheric pressure; conveying the molten, and optionally solidified, product to a continuous melt processing device, such as a single or twin screw extruder; The melt processing equipment can subject the molten product to heat, mixing, and reduced pressure to remove volatile species and maintain the product in a molten state.
[0026] The resulting composition has a weight average molecular weight (polystyrene equivalent molecular weight measured by gel permeation chromatography) of at least 10,000 g / mole, and a crystallinity of 5% or less, or 1% or less, as determined by differential scanning calorimetry.
[0027] In some embodiments, a second polymer type may be added to the melt processing equipment in addition to the polyester resin product.
[0028] Some embodiments disclosed herein are set forth in the claims, and any combination of these embodiments (or portions thereof) can define an embodiment.
[0029] Foamable Composition In one embodiment, a foamable composition is provided that includes the amorphous polyester or copolyester resin and one or more blowing agents. In a particular embodiment, the blowing agent is selected from one or more physical blowing agents, such as pentane hydrocarbons, hydrofluoroolefins, carbon dioxide, nitrogen, oxygen, water, alcohols such as methanol and ethanol, ketones including acetone, ethers such as dimethyl ether and diethyl ether, halogenated hydrocarbons such as ethylene chloride and methylene chloride, or olefins such as pentene, or combinations thereof. Examples of suitable chemical blowing agents are azides such as azodicarbonamide (AZNP), 5-phenyltetrazole (5PT), or a mixture of citric acid and bicarbonate.
[0030] Solid Expandable Beads In another embodiment of the present invention, there are provided solid expandable beads made from the expandable compositions disclosed herein.
[0031] Foam products The present invention further provides a foamed article comprising the foamable composition described above, the foamed article being made by (a) extrusion foaming of any of the foamable compositions, or (b) bead expansion of solid expandable beads described above. Extrusion foaming and bead expansion are well known terms in the foamed article art. In some embodiments, the foamed article has a foam strength of 96 kg / m 3 (6pcf) or less, or 80kg / m 3 (5pcf) or less, or 40kg / m 3 (2.5 pcf) or less.
[0032] Test Method Differential Scanning Calorimetry (DSC) Method A: The sample was heated from 30°C to 300°C at a rate of 10°C / min under a nitrogen environment, then cooled back to 30°C at 10°C / min. The sample was then heated from 30°C to 300°C at 10°C / min twice. The second heating scan was used to measure the glass transition temperature (Tg) and any heat of fusion (Tm), which is related to crystallinity. The inflection point was used to designate Tg. Tm was determined by integrating any area representing a baseline deviation from 175°C to 225°C. This method was used for all examples, both before and after foaming attempts.
[0033] Gel Permeation Chromatography (GPC) Method B: Samples were dissolved in hexafluoroisopropanol (HFIP) at 40mg / ml. After shaking for 24 hours at room temperature, the samples were completely dissolved in HFIP. Once dissolved in HFIP, the samples were diluted to 2mg / ml with chloroform and filtered through a 0.2um PTFE filter. The samples were then passed through a pair of Mixed C GPC columns at 1ml / min in chloroform mobile phase. The injection volume was 50 microliters and the temperature was kept at 35°C. UV (263nm) and IR detectors were used for detection and a series of polystyrene (PS) molecular weight standards were used for molecular weight calibration. All molecular weights reported are PS equivalent molecular weights.
[0034] Foam Density Measurement: This was determined according to ASTM method D-1622-03.
[0035] Foamability Evaluation Method C: To evaluate the foamability of the comparative and inventive examples, the samples were compression molded (25 tons of pressure for 5 minutes at 180°C) into a 1.3 mm thick film. A portion of the pressed film (approximately 7 mm x 7 mm in area) was placed in a pressure vessel preheated to 125°C. The flask was placed in a metal bath preheated to a set temperature of 125°C. The vessel was then pressurized to 1000 psi using carbon dioxide and the sample was immersed for 3-4 hours to allow the gas to dissolve in the polymer. The pressure was then rapidly released to induce foaming in the sample. Successful foaming was determined by visual observation of void formation in the polymer sample and a corresponding increase in sample volume of at least 50%. EXAMPLES
[0036] Comparative example A: Semi-crystalline PET (Certene 8080 supplied by Muehlstein) was pressed into a film and tested for foamability using the method described above, except the press temperature was 280°C. Upon application of vacuum, the sample was observed to not increase in volume and to be very opaque white in appearance. DSC of the sample was found to contain a substantial melting peak (>20 J / g) indicative of crystallinity.
[0037] Comparative example B: Amorphous PET (Altester 45 supplied by Mitsubishi Gas Chemical) was pressed into a film and tested for foamability using the method described above, except that only 800 psi CO2 was used and the soak time was 12 hours. Upon depressurization, the sample was not observed to increase in volume and had a very opaque white appearance. DSC of the sample was found to contain a substantial melting peak (>20 J / g heat of fusion).
[0038] Example 1: Reaction of polyester with cyclohexanedimethanol and terephthalic acid Virgin poly(ethylene terephthalate) (10 g) supplied by Muehlstein was added to a 100 ml glass reactor at room temperature. Next, 3.7 g of terephthalic acid (supplied by Sigma Aldrich), 3.3 g of cyclohexanedimethanol (supplied by Sigma Aldrich), and 0.013 g of antimony trioxide (supplied by Sigma Aldrich) were added to the reactor. The reactor was sealed and purged with nitrogen for approximately 20 minutes. A glass stirrer was used to mix the reactor contents via overhead mixing at approximately 150 rpm. The reactor headspace was then evacuated to -28.9 inches Hg and backfilled with nitrogen for three cycles. The reactor contents were then gradually heated to 285°C under nitrogen over a period of approximately 1 hour. The contents were held at 285°C for an additional 90 minutes. The pressure in the vessel was then reduced by pulling a vacuum, reaching -28.8 inches Hg. The reaction continued for approximately 3.5 hours at 285°C under vacuum. Volatile species were collected by a short path distillation column and condenser flask cooled with dry ice. To stop the reaction, stirring and heating were discontinued and the reactor was purged with nitrogen and returned to atmospheric pressure. The contents were allowed to cool to ambient temperature (nominal 20-25°C) overnight. The final mole % cyclohexanedimethanol (relative to total diol content) was 30%.
[0039] Differential scanning calorimetry (DSC) was performed on the final product, which showed no crystallinity and a Tg of 79°C.
[0040] To assess foamability, samples were pressed into a film and tested for foamability using the method described above. The sample expanded in volume and showed evidence of pore formation, indicating successful foaming. DSC was run on the material after foaming and no evidence of crystallinity was detected as heat of fusion peaks present in the first heating scan of the sample.
[0041] Example 2: Reaction of polyester with cyclohexanedimethanol Unused poly(ethylene terephthalate) (10 g) supplied by Muehlstein was added to a 100 ml glass reactor at room temperature. Next, 2.3 g of cyclohexanedimethanol (supplied by Sigma Aldrich) and 0.012 g of antimony trioxide (supplied by Sigma Aldrich) were added to the reactor in amounts. The reactor was sealed and purged with nitrogen for approximately 20 minutes. The reactor contents were mixed via overhead mixing at approximately 150 rpm using a glass stirrer. The reactor headspace was then evacuated to -28.6 inches Hg and backfilled with nitrogen for three cycles. The reactor contents were then gradually heated to 285°C under nitrogen over a period of approximately 1 hour. The contents were held at 285°C for an additional 90 minutes. The pressure in the vessel was then reduced by pulling a vacuum, reaching -28.5 inches Hg. The reaction continued for approximately 3.5 hours at 285°C under vacuum. Volatile species were collected by a short-path distillation column and condenser flask cooled with dry ice. To stop the reaction, stirring and heating were discontinued and the reactor was purged with nitrogen back to atmospheric pressure. The contents were allowed to cool to ambient temperature (nominal 20-25 °C) overnight. The final target mole % cyclohexanedimethanol (relative to total diol content) was 30%.
[0042] Differential scanning calorimetry (DSC) was performed on the final product, which showed no crystallinity and a Tg of 76°C.
[0043] Example 3: Reaction of polyester with isosorbide and terephthalic acid Virgin poly(ethylene terephthalate) (10 g) supplied by Muehlstein was added to a 100 ml glass reactor at room temperature. Next, 2.85 g of terephthalic acid (supplied by Sigma Aldrich), 2.55 g of isosorbide (supplied by Sigma Aldrich), and 0.014 g of antimony trioxide (supplied by Sigma Aldrich) were added to the reactor in amounts. The reactor was sealed and purged with nitrogen for approximately 20 minutes. A glass stirrer was used to mix the reactor contents via overhead mixing at approximately 150 rpm. The reactor headspace was then evacuated to -28.6 inches Hg and backfilled with nitrogen for three cycles. The reactor contents were then gradually heated to 285°C under nitrogen over a period of approximately 1 hour. The contents were held at 285°C for an additional 90 minutes. The pressure in the vessel was then reduced by pulling a vacuum until -28.6 inches Hg was reached. The reaction continued under vacuum at 285°C for approximately 3.5 hours. Volatile species were collected by a short-path distillation column and condenser flask cooled with dry ice. To stop the reaction, stirring and heating were discontinued and the reactor was purged with nitrogen and returned to atmospheric pressure. The contents were allowed to cool to ambient temperature (nominal 20-25°C) overnight. The final mole % isosorbide (relative to total diol content) was 25%.
[0044] DSC run on the final product prior to foaming attempts showed no crystallinity and a Tg of 107°C.
[0045] Example 4: Reaction of polyester with isosorbide Unused poly(ethylene terephthalate) (15 g) supplied by Muehlstein was added to a 100 ml glass reactor at room temperature. Then, 2.9 g of isosorbide (supplied by Sigma Aldrich) and 0.02 g of antimony trioxide (supplied by Sigma Aldrich) were added to the reactor in amounts. The reactor was sealed and purged with nitrogen for approximately 20 minutes. The reactor contents were mixed via overhead mixing at approximately 150 rpm using a glass stirrer. The reactor headspace was then evacuated to -28.8 inches Hg and backfilled with nitrogen for three cycles. The reactor contents were then gradually heated to 285°C under nitrogen over a period of approximately 1 hour. The contents were held at 285°C for an additional 90 minutes. The pressure in the vessel was then reduced by pulling a vacuum, reaching -28.7 inches Hg. The reaction continued for approximately 3.5 hours at 285°C under vacuum. Volatile species were collected by a short-path distillation column and condenser flask cooled with dry ice. To stop the reaction, stirring and heating were discontinued and the reactor was purged with nitrogen back to atmospheric pressure. The contents were allowed to cool to ambient temperature (nominal 20-25°C) overnight. The final target mole % isosorbide (relative to total diol content) was 25%.
[0046] DSC run on the final product prior to foaming attempts showed no crystallinity and a Tg of 97°C.
[0047] Example 5: Reaction of polyester with cyclobutanediol and terephthalic acid Unused poly(ethylene terephthalate) (6 g) supplied by Muehlstein was added to a 100 ml glass reactor at room temperature. Next, 4.6 g of terephthalic acid (supplied by Sigma Aldrich), 5.2 g of cyclobutanediol (supplied by Sigma Aldrich), and 0.018 g of antimony trioxide (supplied by Sigma Aldrich) were added to the reactor in amounts. The reactor was sealed and purged with nitrogen for approximately 20 minutes. The reactor contents were mixed via overhead mixing at approximately 150 rpm using a glass stirrer. The reactor headspace was then evacuated to -28.9 inches Hg and backfilled with nitrogen for three cycles. The reactor contents were then gradually heated to 285°C under nitrogen over a period of approximately 1 hour. The contents were held at 285°C for an additional 90 minutes. The pressure in the vessel was then reduced by pulling a vacuum, reaching -29 inches Hg. The reaction continued for approximately 3.5 hours at 285°C under vacuum. Volatile species were collected by a short-path distillation column and condenser flask cooled with dry ice. To stop the reaction, stirring and heating were discontinued and the reactor was purged with nitrogen back to atmospheric pressure. The contents were allowed to cool to ambient temperature (nominal 20-25 °C) overnight. The final mole % cyclobutanediol (relative to the total diol content) was 50%.
[0048] A DSC was run on the product prior to foaming attempts, which showed no crystallinity and a Tg of 107°C.
[0049] To assess foamability, samples were pressed into films and tested for foamability using the method described above. The samples showed evidence of pore formation, indicating successful foaming. DSC was run on the material after foaming and no evidence of crystallinity was detected as heat of fusion peaks present in the first heating scan of the sample.
[0050] Example 6: Reaction of recycled polyester with cyclohexanedimethanol and terephthalic acid Recycled polyester was obtained in the form of clear pellets from Clean Tech Recyclers (Dundee, MI). Recycled PET (10 g) was added to a 100 ml glass reactor at room temperature. The following amounts were then added to the reactor: 3.8 g terephthalic acid (supplied by Sigma Aldrich), 3.4 g cyclohexanedimethanol (supplied by Sigma Aldrich), and 0.013 g antimony trioxide (supplied by Sigma Aldrich). The reactor was sealed and purged with nitrogen for approximately 20 minutes. A glass stirrer was used to mix the reactor contents via overhead mixing at approximately 150 rpm. The reactor headspace was then evacuated to -28.7 inches Hg and backfilled with nitrogen for three cycles. The reactor contents were then gradually heated to 285°C under nitrogen over a period of approximately 1 hour. The contents were held at 285°C for an additional 90 minutes. The pressure in the vessel was then reduced by pulling a vacuum, reaching -28.8 inches Hg. The reaction continued for approximately 3.5 hours at 285°C under vacuum. Volatile species were collected by a short path distillation column and condenser flask cooled with dry ice. To stop the reaction, stirring and heating were discontinued and the reactor was purged with nitrogen and returned to atmospheric pressure. The contents were allowed to cool to ambient temperature (nominal 20-25°C) overnight. The final mole % cyclohexanedimethanol (relative to total diol content) was 30%.
[0051] Differential scanning calorimetry (DSC) was performed on the final product, which showed no crystallinity and a Tg of 79°C.
[0052] To assess foamability, samples were pressed into films and tested for foamability using the method described above. The samples showed evidence of pore formation, indicating successful foaming. DSC was run on the material after foaming and no evidence of crystallinity was detected as heat of fusion peaks present in the first heating scan of the sample.
[0053] Example 7: Reaction of recycled polyester with isosorbide and terephthalic acid Recycled polyester was obtained in the form of clear pellets from Clean Tech Recyclers (Dundee, MI). Recycled PET (10 g) was added to a 100 ml glass reactor at room temperature. The following amounts were then added to the reactor: 2.87 g terephthalic acid (supplied by Sigma Aldrich), 2.57 g isosorbide (supplied by Sigma Aldrich), and 0.016 g antimony trioxide (supplied by Sigma Aldrich). The reactor was sealed and purged with nitrogen for approximately 20 minutes. A glass stirrer was used to mix the reactor contents via overhead mixing at approximately 150 rpm. The reactor headspace was then evacuated to -28.8 inches Hg and backfilled with nitrogen for three cycles. The reactor contents were then gradually heated to 285°C under nitrogen over a period of approximately 1 hour. The contents were held at 285°C for an additional 90 minutes. The pressure in the vessel was then reduced by pulling a vacuum, reaching -28.9 inches Hg. The reaction continued under vacuum for approximately 3.5 hours. Volatile species were collected by a short-path distillation column and condenser flask cooled with dry ice. To stop the reaction, stirring and heating were discontinued and the reactor was purged with nitrogen back to atmospheric pressure. The contents were allowed to cool to ambient temperature (nominal 20-25°C) overnight. The final mole % isosorbide (relative to total diol content) was 25%.
[0054] DSC run on the final product prior to foaming attempts showed no crystallinity and a Tg of 106°C.
[0055] To assess foamability, samples were pressed into films and tested for foamability using the method described above. The samples showed evidence of pore formation, indicating successful foaming. DSC was run on the material after foaming and no evidence of crystallinity was detected as heat of fusion peaks present in the first heating scan of the sample.
[0056] Example 8: Reaction of Polyester with Unoxol (a 1:1 blend of 1,3 cyclohexanedimethanol and 1,4 cyclohexanedimethanol isomers) and Isophthalic Acid Virgin poly(ethylene terephthalate) (9.7 g) supplied by Muehlstein was added to a 100 ml glass reactor at room temperature. Then, 2.8 g of terephthalic acid (supplied by Sigma Aldrich), 2.5 g of Unoxol (cyclohexane dimethanol mixed isomers supplied by Dow Chemical), and 0.013 g of antimony trioxide (supplied by Sigma Aldrich) were added to the reactor in the amounts shown. The reactor was sealed and purged with nitrogen for about 20 minutes. The reactor contents were mixed via overhead mixing at about 160 rpm using a glass stirrer. The reactor headspace was then evacuated to 0 mbar and backfilled with nitrogen for three cycles. The reactor contents were then gradually heated to 285° C. under nitrogen over a period of about 1 hour. The contents were held at 285° C. for an additional 45 minutes. The pressure in the vessel was then reduced by pulling a vacuum until 0 mbar was reached. The reaction continued for approximately 3.5 hours at 285°C under vacuum. Volatile species were collected by a short path distillation column and condenser flask cooled with dry ice. To stop the reaction, stirring and heating were discontinued and the reactor was purged with nitrogen back to atmospheric pressure. The contents were allowed to cool to ambient temperature (nominal 20-25°C) overnight. The final mole % cyclohexanedimethanol (based on total diol content) was 25%. The final mole % isophthalic acid (based on total diol content) was 25%.
[0057] DSC run on the final product prior to foaming attempts showed no crystallinity and a Tg of 72°C.
[0058] To evaluate foamability, samples were pressed into films and tested for foamability using the method described above. The samples showed evidence of pore formation, indicating successful foaming. After foaming, the samples were measured for crystallinity using DSC. An initial heating scan was used to determine if crystallinity had formed. No evidence of crystallinity was detected (temperature range 125°C - 225°C).
[0059] The molecular weights of the foamable resins are summarized in Table 1.
[0060] [Table 1] (Aspect) (Aspect 1) a crystalline or semi-crystalline polyester or copolyester, optionally obtained from recycled waste streams; at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride; Catalyst and An amorphous polyester or copolyester composition comprising the reaction product of The amorphous composition has a weight average molecular weight, measured by gel permeation chromatography, of at least 10,000 g / mole, calculated as polystyrene equivalent. Amorphous polyester or copolyester compositions. (Aspect 2) 2. The amorphous composition of embodiment 1, wherein the polyester is polyethylene terephthalate, polyethylene terephthalate glycol, or a polyester whose major diol component is ethylene glycol, propylene glycol, 1,4-butanediol, spiro glycol, or a blend thereof. (Aspect 3) 2. The amorphous composition of embodiment 1, wherein the at least one aromatic diacid monomer is phthalic acid, terephthalic acid, isophthalic acid, or 2,5-furandicarboxylic acid, or a combination thereof. (Aspect 4) 2. The amorphous composition of embodiment 1, wherein the at least one diol is ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, butylene glycol, 1,4-butanediol, spiroglycol, isosorbide, cyclohexanedimethanol, or cyclobutanediol, or a combination thereof. (Aspect 5) 2. The amorphous composition of embodiment 1, wherein the catalyst is or includes titanium tetrabutoxide, cerium(III) acetate, tetraisopropyl titanate, antimony trioxide, or a tin-based organometallic complex. (Aspect 6) 2. The amorphous composition of embodiment 1, having a Tg of at least 75° C. (Aspect 7) The amorphous composition according to aspect 4, wherein the cyclohexanedimethanol is 1,4-cyclohexanedimethanol present in an amount of 20 to 40 mol % of the total diol content. (Aspect 8) 5. The amorphous composition of aspect 4, wherein the isosorbide is present in an amount of 15 to 100 mol % of the total diol content. (Aspect 9) The cyclobutanediol is present in an amount of 45 to 55 mole % of the total diol content. 2 5. The amorphous composition of embodiment 4, wherein the -4-tetramethyl-1-3-cyclobutanediol. (Aspect 10) 5. The amorphous composition of embodiment 4, wherein the cyclohexanedimethanol is 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, or blends thereof, present in an amount from 20 to 30 mol % when combined with isophthalic acid or terephthalic acid, or blends thereof, present in an amount from 20 to 30 mol %. (Aspect 11) 2. A foamable composition comprising the amorphous polyester or copolyester resin of embodiment 1 and one or more blowing agents. (Aspect 12) 12. The foamable composition according to claim 11, wherein the foamable composition is in the form of solid beads. (Aspect 13) 12. The foamable composition of claim 11, wherein the blowing agent is selected from one or more pentane hydrocarbons, one or more halogenated hydrocarbons, one or more hydrofluoroolefins, alcohols, ketones, ethers, olefins, carbon dioxide, water, or combinations thereof. (Aspect 14) 96 kg / m produced by extrusion foaming of the foamable composition according to embodiment 11 or expansion of solid beads according to embodiment 12. 3 (6 pcf) or less. (Aspect 15) A method for producing an amorphous polyester foamable resin composition, comprising the steps of: combining crystalline or semi-crystalline polyester, optionally obtained from recycled waste streams, with at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride in a reactor at room temperature in the presence of a catalyst; sealing and purging the reactor with an inert gas; mixing the contents; venting volatile components from the reactor; flushing the reactor with an inert gas at least once; increasing the temperature of the reactor to 250-350° C. for a period of 30-90 minutes; mixing the combination of molten materials; maintaining a temperature of 250-350°C for 20-150 minutes; evacuating the reactor to below minus 25 inches of mercury; continuing the reaction at a temperature of 250-350° C. for 100-300 minutes, optionally removing volatile species via a distillation column; stopping the reaction by stopping mixing, purging the reactor with an inert gas, returning the reactor to atmospheric pressure, and reducing the temperature to below 100°C; Including, The resulting composition has a weight average molecular weight of at least 10,000 g / mole (polystyrene equivalent molecular weight) as measured by gel permeation chromatography, and a crystallinity of 5% or less as determined by differential scanning calorimetry. A method for producing an amorphous polyester foamable resin composition.
Claims
1. a crystalline polyester or copolyester, optionally obtained from recycled waste streams; at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride; Catalyst and An amorphous polyester or copolyester composition comprising the reaction product of the amorphous composition has a weight average molecular weight, measured by gel permeation chromatography, of at least 10,000 g / mole, calculated as polystyrene equivalent; The sample was heated from 30° C. to 300° C. at a rate of 10° C. / min in a nitrogen environment, then cooled back to 30° C. at 10° C. / min. The sample was then heated from 30° C. to 300° C. at 10° C. / min twice, and the second heating scan was used to determine the glass transition temperature (T g ) and a Tg of at least 75° C. is determined by a measurement method that uses an inflection point to specify the Tg. g , and having a crystallinity of 5% or less as determined by differential scanning calorimetry; Amorphous polyester or copolyester compositions.
2. 2. The amorphous composition of claim 1, wherein the polyester is polyethylene terephthalate, polyethylene terephthalate glycol, or a polyester whose major diol component is ethylene glycol, propylene glycol, 1,4-butanediol, spiro glycol, or a blend thereof.
3. 2. The amorphous composition of claim 1, wherein the at least one aromatic diacid monomer is phthalic acid, terephthalic acid, isophthalic acid, or 2,5-furandicarboxylic acid, or a combination thereof.
4. 2. The amorphous composition of claim 1, wherein the at least one diol is ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, butylene glycol, 1,4-butanediol, spiroglycol, isosorbide, cyclohexanedimethanol, or cyclobutanediol, or a combination thereof.
5. 10. The amorphous composition of claim 1, wherein the catalyst is or comprises titanium tetrabutoxide, cerium (III) acetate, tetraisopropyl titanate, antimony trioxide, or a tin-based organometallic complex.
6. 10. The amorphous composition of claim 1 having a crystallinity of 1% or less as determined by differential scanning calorimetry.
7. 5. The amorphous composition of claim 4, wherein the cyclohexanedimethanol is 1,4-cyclohexanedimethanol present in an amount of 20 to 40 mole percent of the total diol content.
8. 5. The amorphous composition of claim 4, wherein the isosorbide is present in an amount of 15 to 100 mole % of the total diol content.
9. 5. The amorphous composition of claim 4, wherein the cyclobutanediol is 2-2-4-4-tetramethyl-1-3-cyclobutanediol present in an amount of 45 to 55 mole % of the total diol content.
10. 5. The amorphous composition of claim 4, wherein the cyclohexanedimethanol is 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, or blends thereof, present in an amount of 20 to 30 mole % when combined with isophthalic acid or terephthalic acid, or blends thereof, present in an amount of 20 to 30 mole %.
11. 10. A foamable composition comprising the amorphous polyester or copolyester composition of claim 1 and one or more blowing agents.
12. 12. The foamable composition of claim 11, wherein the foamable composition is in the form of solid beads.
13. 12. The foamable composition of claim 11, wherein the blowing agent is selected from one or more pentane hydrocarbons, one or more halogenated hydrocarbons, one or more hydrofluoroolefins, alcohols, ketones, ethers, olefins, carbon dioxide, water, or combinations thereof.
14. 96 kg / m produced by extrusion foaming of the foamable composition of claim 11 or expansion of the solid beads of claim 12. 3 (6 pcf) or less.
15. A method for producing an amorphous polyester foamable resin composition, comprising the steps of: combining crystalline polyester, optionally obtained from a recycled waste stream, with at least one diol or aromatic diacid or ester of a diacid or hydroxycarboxylic acid or lactone or dianhydride in a reactor at room temperature in the presence of a catalyst; sealing and purging the reactor with an inert gas; mixing the contents; venting volatile components from the reactor; flushing the reactor with an inert gas at least once; increasing the temperature of the reactor to 250-350° C. for a period of 30-90 minutes; mixing a combination of molten materials; maintaining a temperature of 280-350° C. for 20-150 minutes; evacuating the reactor to below minus 25 inches of mercury; continuing the reaction at a temperature of 250-350° C. for 100-300 minutes, optionally removing volatile species via a distillation column; stopping the reaction by stopping mixing, purging the reactor with an inert gas, returning the reactor to atmospheric pressure, and reducing the temperature to below 100°C; adding a blowing agent; Including, The resulting composition has a weight average molecular weight of at least 10,000 g / mole (polystyrene equivalent molecular weight) as measured by gel permeation chromatography; The sample was heated from 30° C. to 300° C. at a rate of 10° C. / min in a nitrogen environment, then cooled back to 30° C. at 10° C. / min. The sample was then heated from 30° C. to 300° C. at 10° C. / min twice, and the second heating scan was used to determine the glass transition temperature (T g ) and measuring the Tg by a measurement method using an inflection point to specify the Tg, g , and having a crystallinity of 5% or less as determined by differential scanning calorimetry; A method for producing an amorphous polyester foamable resin composition.
Citation Information
Patent Citations
Foamable microbiodegradable copolyester composition
JP2000510189A
Polymer manufacturing process
JP2010522805A
Polyester for covering
JP2013510917A
Aliphatic-aromatic copolyesters, compositions, and methods for producing copolyesters
JP2014525505A
Polymer Manufacturing Process
US20080236443A1